Kajian Tingkat Kerentanan Longsor Menggunakan Sistem Informasi Geografis Kecamatan Monano, Kabupaten Gorontalo Utara - Fitria Maharani Putri Iwan Noho; Sri Maryati; Muhammad Kasim (Universitas Negeri Gorontalo, 2025)
Gorontalo Province has areas that are prone to landslides, especially in North Gorontalo Regency. This study has two main objectives, namely identifying the lithology that makes up the research area and analyzing the level of landslide vulnerability in area. This study uses the Multi Criteria Evaluation (MCE) method with the use of GIS analysis to achieve its objectives. Determination of the level of landslide vulnerability is carried out by overlaying parameters such as lithology, straightness density, slope gradient, soil type, rainfall and land use. The lithology that makes up the research area consists of andesite, agglomerate, sandstone and alluvial deposit units. Based on the results of the analysis, landslide vulnerability in the research area can be categorized into 3 classes, namely. Low landslide susceptibility class (34.13 km2), medium landslide susceptibility class (66.89 km2) and high landslide susceptibility class (19.65 km2)